2016
DOI: 10.1097/acm.0000000000001232
|View full text |Cite
|
Sign up to set email alerts
|

Race Matters? Examining and Rethinking Race Portrayal in Preclinical Medical Education

Abstract: Critical examination of "health disparities" is gaining consideration in medical schools across the United States, often as elective curricula that supplement required education. However, there is disconnect between discussions of race and disparities in these curricula and in core science courses. Specifically, required preclinical science lecturers often operationalize race as a biological concept, framing racialized disparities as inherent in bodies. A three- and five-month sampling of lecture slides at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(171 citation statements)
references
References 39 publications
2
169
0
Order By: Relevance
“…This happens in medicine too. To take just one example, spirometry value calculators, which measure lung function, sometimes include ‘race corrections’ because in 1864 a large study concluded that white soldiers had higher lung capacity than black soldiers and yet there is no modern evidence that lung function varies based on the colour of one's skin.…”
Section: Discussionmentioning
confidence: 99%
“…This happens in medicine too. To take just one example, spirometry value calculators, which measure lung function, sometimes include ‘race corrections’ because in 1864 a large study concluded that white soldiers had higher lung capacity than black soldiers and yet there is no modern evidence that lung function varies based on the colour of one's skin.…”
Section: Discussionmentioning
confidence: 99%
“…While some medical schools have courses on racial disparities in health, critical race theory to help contextualize racial health disparities is not a requirement. In fact, in most medical school curricula, race is framed as biological or as a biological risk factor, implying that racial disparities in health are innate and can be explained without implicating racism . This fosters pathologizing race rather than racism, whereas racism is the risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in most medical school curricula, race is framed as biological or as a biological risk factor, implying that racial disparities in health are innate and can be explained without implicating racism. [30][31][32][33] This fosters pathologizing race rather than racism, whereas racism is the risk factor. Naming racism in medical education, health services research and policy, and how it is distinct from race as a category can advance efforts to reduce racial health inequities.…”
Section: Center the Marginsmentioning
confidence: 99%
“…This may have important social consequences, and not just for research. For example, Tsai et al 6 reported that race was used as an unexplained, definitive category in the teaching of medical students in the USA, and that essentialist and misleading ideas about race were being reproduced through this education. The same is true of the training of health professionals in many other countries.…”
Section: Explaining the Influence Of Race On Health And Diseasementioning
confidence: 99%